A futuristic survey of the effects of LU/LC change on stream flow by CA–Markov model: a case of the Nekarood watershed, Iran. Issue 10 (15th June 2021) - Tavangar, Sh.; Moradi, H.; Massah Bavani, A.; Gholamalifard, M.
Abstract: Land use (LU) or land cover (LC) is a critical factor dictating the amount of available water in runoff and groundwater. LU/LC Land use (LU) or land cover (LC) is a critical factor which can determine amount of available water in runoff and groundwater. In this study future effect of LU/LC change on stream flow in Nekarood watershed is investigated by Soil Water Assessment Tool (SWAT). Land use maps (1986–2016) based on Landsat TM and ETM+ satellite imagery are used. Furthermore, land use projection is performed by CA-Markov for the future period of 2016–2030. According to the results, agriculture and residential land use are increased by 40%, 28%, 38% and 31% respectively, and forest area is reduced by 12% and 6% during 1986–2001 and 2001–2016, respectively. Moreover, land use projection results showed that from 2016 to 2030 forest area will decrease by 6%, residential areas and agricultural will increase by 34% and 19%, respectively.